Dekonstruksi patriarki khaled hosseini dalam novel a thousand splendid suns - Endang Suciati (Unipdu Jombang, 2017)
Endang SuciatiUniversitas Pesantren Tinggi Darul Ulum Jombangendangsuciati@fbs.unipdu.ac.id AbstractThe culture of patriarchy can be found in many quotations in A Thousand Splendid Suns novel. This kind of culture seems to dominate the woman. It can be seen that woman is considered weak. On the other hand, this novel also depicts the strength of woman that woman has braveness to fight againt and to control the man. Thus, the problem is about how this cultural of patriarchy is indeed deconstructed by this novel. This novel was analyzed using the concept of patriarchy by Kate Millet and deconstruction about hirarchy. The result shows that there is reversal of hirarchy between the man (Taliban leader, Rasheed, and Jalil) who are considered strong and powerfull and the women (Mariam, Laila, and Jalil’s wives) who previously are considered subordinated. They are the women who are strong, have braveness to face the truth, responsibility, and have power to control the men. It shows that it is true that there is deconstruction about the culture of patriarchy which previously has been contructed by Khaleed Hossaeni in the novel.Keywords: patriarchy, deconstruction, A Thousand Splendid Suns